2018
DOI: 10.1017/jfm.2018.309
|View full text |Cite
|
Sign up to set email alerts
|

Vortex-induced vibration of a transversely rotating sphere

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 18563To link to this article : DOI : URL :Any correspondence concerning this service should be sent to the repository administrator: staff-oatao@listes-diff.inp-toulouse.fr AbstractVortex-induced vibration (VIV) of a sphere is one of the most basic fluid-structure interaction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Thus, it can be assumed that the sphere undergoes a very small amount of rotation when it is also subjected to torsion. Our previous study (Rajamuni et al 2018b) and the study of Sareen et al (2018a) investigated the VIV response of an elastically mounted sphere under a forced rotation. Both of these studies found that the effect of rotation is negligible on the VIV response of the sphere, for small rotation rates.…”
Section: Fiv Response Of a Tethered Spherementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it can be assumed that the sphere undergoes a very small amount of rotation when it is also subjected to torsion. Our previous study (Rajamuni et al 2018b) and the study of Sareen et al (2018a) investigated the VIV response of an elastically mounted sphere under a forced rotation. Both of these studies found that the effect of rotation is negligible on the VIV response of the sphere, for small rotation rates.…”
Section: Fiv Response Of a Tethered Spherementioning
confidence: 99%
“…In addition, mode II also appears sensitive to disturbances and other factors. For example, the experimental study of Sareen et al (2018a) and the computational study of Rajamuni et al (2018b) found that the mode II response weakens if even weak rotation (in the transverse direction) is imposed on the sphere. In particular, they observed a considerable reduction in the maximum oscillation amplitude and a narrowing of the synchronization regime.…”
Section: Robustness Of Modes I and Iimentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the amplitude of mode II was observed to be about twice that of mode I. In contrast to these experimental observations at high Reynolds numbers, the transition between modes I and II was obscure in the amplitude response at low Reynolds numbers (Behara, Borazjani & Sotiropoulos 2011; Behara & Sotiropoulos 2016; Rajamuni, Thompson & Hourigan 2018 a , b ). The recent study of Rajamuni, Thompson & Hourigan (2020 b ) numerically investigated vibration modes of a tethered sphere, and found that the effect of Reynolds number on the modes I and II regimes was significant over the Reynolds number range , although it was found to be insignificant beyond that range for in the experimental studies of Govardhan & Williamson (2005).…”
Section: Introductionmentioning
confidence: 67%
“…This solver with a similar computational set-up was used for the computational study of Rajamuni, Thompson & Hourigan (2016) and Rajamuni et al. (2018 b ) to examine the effect of transverse rotation on the FIV of a sphere. In addition, Rajamuni et al.…”
Section: Numerical Methodology and Validationmentioning
confidence: 99%